Numerical Simulation of Mixing Characteristics in the Eccentric Rotor Extruder with Different Process Conditions and Structural Parameters - De-jun Fan; Ming-kai Yang; Zhi-gao Huang; Jin-song Wen (Advances in Polymer Technology)
Numerical simulation was performed with the computational fluid dynamics analysis software POLYFLOW to investigate the influence of different process conditions and structural parameters on mixing characteristics of the eccentric rotor extruder. The intensity of shear and elongational flow strengthened when the rotational speed increased, but the time for material to stay in the extruder will be reduced. At the same time, the increase of radius and eccentricity could effectively promote the mixing performance. On the contrary, the mixing capacity reduced with the increase of the pitch. The results can be useful to optimize the structure design and guide production.